Distribution of microbial community structure during bioremediation treatment of herbicide/Dioxin contaminated soil at field small scale - Huu, Nguyen Ba; Ha, Dang Cam (Academia Journal of Biology, 2014)
Distribution of microbial community structure during bioremediation treatment of herbicide/Dioxin contaminated soil at field small scale